MAIR‐II deficiency ameliorates cardiac remodelling post‐myocardial infarction by suppressing TLR9‐mediated macrophage activation. Issue 24 (2nd November 2020) - Yonebayashi, Saori; Tajiri, Kazuko; Murakoshi, Nobuyuki; Xu, Dongzhu; Li, Siqi; Feng, Duo; Okabe, Yuta; Yuan, Zixun; Song, Zonghu; Aonuma, Kazuhiro; Shibuya, Akira; Aonuma, Kazutaka; et al.
Abstract: Macrophages are fundamental components of inflammation in post‐myocardial infarction (MI) and contribute to adverse cardiac remodelling and heart failure. However, the regulatory mechanisms in macrophage activation have not been fully elucidated. Previous studies showed that myeloid‐associated immunoglobulin–like receptor II (MAIR‐II) is involved in inflammatory responses in macrophages. However, its role in MI is unknown. Thus, this study aimed to determine a novel role and mechanism of MAIR‐II in MI. We first identified that MAIR‐II–positive myeloid cells were abundant from post‐MI days 3 to 5 in infarcted hearts of C57BL/6J (WT) mice induced by permanent left coronary artery ligation. Compared to WT, MAIR‐II–deficient ( Cd300c2 −/− ) mice had longer survival, ameliorated cardiac remodelling, improved cardiac function and smaller infarct sizes. Moreover, we detected lower pro‐inflammatory cytokine and fibrotic gene expressions in Cd300c2 −/− ‐infarcted hearts. These mice also had less infiltrating pro‐inflammatory macrophages following MI. To elucidate a novel molecular mechanism of MAIR‐II, we considered macrophage activation by Toll‐like receptor (TLR) 9–mediated inflammation. In vitro, we observed that Cd300c2 −/− bone marrow–derived macrophages stimulated by a TLR9 agonist expressed less pro‐inflammatory cytokines compared to WT. In conclusion, MAIR‐II may enhance inflammation via TLR9‐mediated macrophage activation in MI, leading to adverse cardiac remodelling and poor prognosis.